An Ultra-Shapeable, Smart Sensing Platform Based on a Multimodal Ferrofluid-Infused Surface - Ahmed, Abdelsalam (Adv Mater, 2019)
The development of wearable, all-in-one sensors that can simultaneously monitor several hazard conditions in a real-time fashion imposes the emergent requirement for a smart and stretchable hazard avoidance sensing platform that is stretchable and skin-like. Multifunctional sensors with these features are problematic and challenging to accomplish. In this context, a multimodal ferrofluid-based triboelectric nanogenerator (FO-TENG), featuring sensing capabilities to a variety of hazard stimulus such as a strong magnetic field, noise level, and falling or drowning is reported. The FO-TENG consists of a deformable elastomer tube filled with a ferrofluid, as a triboelectric layer, surrounded by a patterned copper wire, as an electrode, endowing the FO-TENG with excellent waterproof ability, conformability, and stretchability (up to 300%). In addition, The FO-TENG is highly flexible and sustains structural integrity and detection capability under repetitive deformations, including bending and twisting. This FO-TENG represents a smart multifaceted sensing platform that has a unique capacity in diverse applications including hazard preventive wearables, and remote healthcare monitoring.